Right time or right person? Investigating the hires of high-growth new ventures - Sven-Olov Daunfeldt; Alexander McKelvie; Hans Seerar Westerberg (Institute of Retail Economics (HFI), 2023)
Hiring new employees is an important part of a new venture's growth. However, we still have limited understanding of the human capital needs of high-growth new ventures, and how their pace of growth relates to whom they hire. We contribute to the literature by investigating 64,404 hires among growing new ventures in Sweden from 2008 to 2015, finding that individuals with higher educational attainment and previous management experience are more likely to be hired by high-growth new ventures. In contrast, we find no indications that unemployed individuals or people that are outside the labor force are more likely to be hired by the fastest growing new ventures. High-growth new ventures are thus more selective in their hiring decisions than new ventures with lower sales growth rates, suggesting that 'the right person' is more important than 'the right time'. These differences in hiring practices are most prevalent during new ventures' first three years of operation and become more negligible as the ventures age.
Keywords: D21; D22; J63; L25; 330; Hiring; High-growth new ventures; Firm growth; Human capital